PERAN GURU KELAS DALAM MENGATASI MASALAH INDIVIDU SISWA KELAS VA SD NEGERI 24 KOTA BENGKULU - Sinta Dwi Gusti; Zubaidah; Heni Putri Rahayu; Lini Susanti; Siska Marsela (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to find out individual problems that exist in students in VA class at SDN 24 Bengkulu City. And for how do homeroom teachers deal with individual problems that exist within themselves in Class V SDN 24 Bengkulu City. This study uses a descriptive qualitative approach. The type of research used is a case study. Data collection techniques: observation techniques, and interviews. The results of the study show that there are personal problems that exist in students including the problem of intellectual intelligence, the process of fast and slow students in capturing learning, problems of delinquency such as mocking, insulting and making noise with friends. The way to deal with it is that the class teacher takes an emotional approach to students, gives more attention, provides intensive additional learning and understands other problems that exist in children. Another problem of children is also found to be family problems such as children who have broken homes.